Synthesis of Tetracyclic systems and (Thio)Ureas from Aminodi(Hetero)Arylamines in the Thieno[3,2-b]Pyridine series - Queiroz, Maria João R. P. (2012)
Foundation for the Science and Technology (FCT–Portugal) for financial support through the Portuguese NMR network (Bruker 400 Avance III-Univ Minho). FCT and FEDER (European Fund for Regional Development)-COMPETE/QREN/EU for financial support through the research centre PEst-C/QUI/UI686/2011, the research project PTDC/QUI-QUI/111060/2009 and the post-doctoral grant of R.C.C. SFRH/BPD/68344/2010.